PERANAN PEMERINTAH DAERAH DALAM PENGENDALIAN PERTUMBUHAN PENDUDUK (Suatu Studi di Badan Keluarga Berencana dan Pemberdayaan Perempuan Kabupaten Kepulauan Talaud) - TATUHE, STEFHEN; LALOMA, ALDEN; Pesoth, Welly (JURNAL ADMINISTRASI PUBLIK, 2016)
ABSTRACT: According to law number 52 of 2009 on population development and family development, demography is the particulars relating to the number, structure, growht, distribution, mobility, deployment, quality, and wlfare conditions relating to political, economic, social, cultural, religious, and neighborhood local.From the above data, the government must take action in order to minimize the amount of populaion growht is very high, and one of the efforts that maximize the role of the agenci or agencies competent in dealing whit population growth. Family planning is one of the government’s efforts to reduce the rate of population growth.Basicalli the popolation growth in the distric talaud ilands can still lacking on the run, this research uses descriptive research methods, data sources/respondents were 17 government official, data collection using questionnaries and open interviews, data analysis used was qualitative descriptive statistical analysis.The results showed: 1). The ifluencing factors in the increase in number of people such as marriage at an early age, lack of public awareness in running the government program and the birth rate is very high. This is what should be a task that must be resolved by the famili planning agencies at both central and district in Talaud Island. 2). The limiting factor in overcoming the problem of population growth rates in the talaud island, and the factors that most hamper is a marriage that is done at an early age as well as the proximity of the child’s birth due to lack maximizing government in overcome problem of overcrowding that threatened districts island talaud even when this rate of growth is not too high and still be in control.Of the above results is concluded that the government’s role in controlling the population growth in the distric Talaud Island in the inplementation are still lacking to participate and perform their duties according to predetermined at the center and in the regions.Of the above conclusion, suggested the government scould carry out duties according to their duty at the center and in the regions and the inplementation of field extension can be done on an ongoing basic as well as the addition of personnel so as to reach all areas dufficult to reach.Keywords: Role, Control, and Population.